AN ELECTRONIC PRESCRIPTION ALERTING SYSTEM-IMPROVING THE DISCHARGE MEDICINES PROCESS. Issue 9 (17th August 2016) - Bevan, Amanda; Patel, Niesh
Abstract : Background: Whilst the prescribing of both in-patient and discharge medicines is electronic, there was no automatic notification to clinical pharmacists when a discharge prescription was ready to be screened. The notification required a member of medical or nursing staff to bleep their pharmacist informing them of a prescription's availability. This manual process led to a delay in pharmacist screening which impacted on discharge. Prescriptions designated for pre-packed or patient's own medicine use were not seen at all by a clinical pharmacist. The initial intention was to develop a text messaging service; however this was not possible due to significant cost implications and its inflexibility. Aim: To decrease the time to clinical pharmacist screening for children's discharge prescriptions. Method: A clinical pharmacist prescription alerting system was designed and implemented. The hospital's eDischarge Summaries are created and stored in the Trust's EPR database. A database query is executed that examines documents that have been signed by a prescriber which contain drug orders. The query runs every 15 minutes, Monday to Friday from 0800–2000. The database query exports a HTML data extract which is then packaged and sent using Exchange. Email was preferred as users access hospital WiFi, only receiving notifications on those laptops or smartphones connected to the Trust's email application. The HTML is embedded within the email body. The email is sent to named individuals within a given distribution list. The function is scalable to support all areas using Trust eDischarge Summaries. The system was introduced in April 2015. Data from before (June 2014–January 2015) and after (June 2015) implementation was compared. Results: Prior to the introduction of an electronic alerting system the average time from a prescriber signing a prescription to clinical pharmacist screening was 93 minutes. Three months after starting the new system this time has reduced to 62 minutes, a reduction of 31 minutes or 33%. During the same time period, the number of discharge prescriptions screened by pharmacists rose from 172 to 218, an increase in workload of 26%. It has been possible to intervene on prescriptions containing errors which the clinical pharmacists would not previously have screened. Conclusion: The use of an electronic messaging system has met its primary aim to decrease the time delay from signing to pharmacist screening it has also increased pharmacist efficiency as evidenced by the increased workload. One limitation of this system is that it requires a regular e-mail check, for available prescriptions. The report runs every 15 minutes, an email is only sent if a prescription is found. The notification of all discharge prescriptions containing medicines has led to the identification of errors which have required intervention, in those prescriptions that a pharmacist would not have previously seen. These interventions have been for children who have received pre-packed antibiotics directly from the wards or for those where we have provided one-stop dispensing. It is hoped to role out this system across other areas of the organisation which should also enjoy this significant improvement in discharge prescription turnaround.